Effects of DPDPE (a specific ?-opioid receptor agonist) and naloxone on hypothalamic monoamine concentrations during the pre-ovulatory LH surge in the rat - Yilmaz, B; Gilmore, DP; Wilson, CA (Scandinavian University Press, 1998)
We have investigated the inter-relationship between the opioid and aminergic systems in the control of secretion of the pro-oestrous LH surge and the involvement of delta-opioid receptor subtypes in this process. Conscious female rats bearing a cannula in the femoral artery were injected i.p. with a selective delta-opioid receptor agonist (DPDPE) either alone or with the opioid antagonist (naloxone) at 1300 h on the day of pro-oestrus. Blood samples were collected hourly between 1500 h and 1900 h, and plasma LH levels were measured by RIB. At the end of this period (1900 h), the animals were autopsied and the concentrations of the amines (noradrenaline (NA), dopamine (DA), 5-hydroxytryptamine (5HT)) and their metabolites (dihydroxyphenolglycol (DHPG) and 5-hydroxyindoleacetic acid (5HIAA), metabolites of NA and 5HT respectively) were determined by HPLC with electrochemical detection in the medial preoptic area, suprachiasmatic nucleus, median eminence and arcuate nucleus. DPDPE abolished the LH surge and concomitantly decreased hypothalamic NA and DHPG concentrations in all the areas examined. The levels of DA, 5HT and 5HIAA were also reduced in all hypothalamic regions studied, except DA and 5HIAA in the suprachiasmatic nucleus, Naloxone reversed these inhibitory effects of the delta-agonist. We conclude that activation of delta-opioid receptors may exert an inhibitory effect on LH release. The effect is probably an indirect one mediated by the monoaminergic systems, as they are suppressed by DPDPE in nearly all the hypothalamic regions studied.
Keywords: Luteinizing-Hormone Release; Biogenic-Amine Turnover; Ovariectomized Rats; Noradrenergic Neurons; Dopaminergic-Neurons; Prolactin Secretion; Preoptic Area; Mu; Serotonin; Catecholamines